Gestión administrativa en la empresa Mundijuegos Sucrursal Babahoyo año 2021 - Cruz Vite, Darla Juliette (2021)
The present investigative work is based on the administrative management of the company Mundijuegos Babahoyo branch, its main objective is to define strategies that improve the current situation in which the company finds itself. The method used in this research is descriptive, which in turn is qualitative and quantitative, where a survey applied to the employees of the company Mundijuegos and an interview with the manager Cesar Gonzales, owner of the same. This project was subject to the research line of financial, administrative, tax, auditing, control framed with subline of companies and public and private institutions